Socio-Demographic Profile of Québec's English-speaking Youth Aged 15-29 - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
This report profiles the situation of English-speaking citizens of Québec who are engaged in the numerous transitions that are typically encountered between the ages of 15 and 29 in the critical passage from childhood to adulthood. Youth is a stage of life characterized by challenges that can be decisive in the quality of life of individuals and their communities and for most Québecers aged 15-29, these milestones are: completing school, gaining occupational experience and even starting a family and establishing a household. This report offers current information organized to support “the village” - from policymakers and program managers to public institutions, community organizations and networks - whose actions impact the lives of minority language youth striving to build their future and the future of all Québec’s citizens.

Initiative sur la jeunesse et la santé mentale : Rapport d'évaluation final : 2021-2024 - Glass, Juniper (Community Health and Social Services Network (CHSSN), 2024)
L’initiative sur la jeunesse et la santé mentale promeut la santé mentale des jeunes Québécois(es) d’expression anglaise en améliorant leur accès aux ressources et aux services et en les faisant participer à la conception et à la mise en oeuvre d’activités qui favorisent leur autonomie et réduisent la stigmatisation de leurs pairs et de leur communauté. Pour la période 2021-2024, l’initiative YMHI a été axée sur la sensibilisation des jeunes, l’acquisition de connaissances et l’adaptation des services et des ressources de santé mentale pour qu’ils soient plus inclusifs, invitants pour les jeunes et adaptés à leur culture afin de rejoindre les jeunes anglophones mal desservis.

Youth Mental Health Initiatiive : Final Evaluation Report : 2021-2024 - Glass, Juniper (Community Health and Social Services Network (CHSSN), 2024)
The Youth Mental Health Initiative promotes the mental health of English-speaking youth by improving their access to resources and services and involving them in the design and implementation of activities that promote their agency and reduce stigma in their peers and community. In 2021-24, YMHI focused on mental health literacy and awareness building with youth while promoting the adaptation of mental health services and resources to be more inclusive, youth-friendly and culturally appropriate to reach underserved English-speaking youth.

Climate Anxiety Among English-Speaking Youth in Québec - Pettem, Alexandre; Rengel, Fernanda (2023)

Swimming Upstream : Investigating the Barriers to Aquatic Equity for Québec’s English-speaking BIPOC Youth Communities - Porras-Gil, Javier Armando (2023)

Community Connections : Youth Perspectives on Mental Health - Youth for Youth Québec (Y4Y Québec) (2023)
Number of pages: 25

[Newsletter] - Youth for Youth Québec (Y4Y Québec) (2023)
Number of pages: 10

[Newsletter] - Youth for Youth Québec (Y4Y Québec) (2023)
Number of pages: 15

A Public Transportation Renaissance in a Post-Pandemic Context - Gherman, Stefan (2023)

Mental Health in the Anthropocene : Climate Anxiety among Québec’s English-speaking Youth - Rengel, Fernanda; Pettem, Alexandre (2023)

Community Connections : Youth Perspectives on Mental Health - Youth for Youth Québec (Y4Y Québec) (2023)
Number of pages: 20

[Newsletter] - Youth for Youth Québec (Y4Y Québec) (2023)
Number of pages: 20

Newsletter - Youth for Youth Québec (Y4Y Québec) (2023)
Number of pages: 23

Residential Precarity : Youth and Housing in Québec’s Urban Centres - Rodriguez, Chloe (Y4Y Québec, 2023)

Residential Precarity: Youth and Housing in Québec’s Urban Centres - Rodriguez, Chloe (2023)

Newsletter - Youth for Youth Québec (Y4Y Québec) (2023)
Number of pages: 18

L’initiative sur la jeunesse et la santé mentale : Rapport d'impcat 2022-2023 - Community Health and Social Services Network (CHSSN) (2023)
Au cours de la deuxième année de l'initiative sur la jeunesse et la santé mentale (surnommée « YMHI »), le CHSSN a soutenu 27 organismes communautaires avec plus de 373 partenariats dans 12 régions du Québec, y compris trois organismes provinciaux, dans le but principal d'améliorer l'accès aux services et aux ressources en matière de santé mentale pour les jeunes d’expression anglaise du Québec âgés de 15 à 29 ans. Chaque organisation s'est efforcée d'identifier les lacunes dans les services de santé mentale pour les jeunes, d'impliquer ces derniers dans la conception des programmes, d'établir des partenariats avec les écoles locales, les services de santé publique et d'autres organisations communautaires, d'adapter, de traduire et de produire des ressources, et d'offrir des activités et des programmes pour les jeunes afin de contribuer à combler certaines lacunes. Grâce à une communauté de pratique et à un soutien individualisé, le CHSSN aide les organismes communautaires à renforcer leurs connaissances, à travailler en réseau et à résoudre les problèmes liés à la mise en oeuvre de leur programme.

Youth Mental Health Initiative : Impact Report 2022-2023 - Community Health and Social Services Network (CHSSN) (2023)
Within the Youth Mental Health Initiative’s (YMHI) second year, CHSSN supported 27 community organizations with over 373 partnerships across 12 regions of Quebec including three provincial organizations, with the central goal of improving the access of mental health services and resources to Quebec’s English-speaking youth between the ages of 15-29. Each organization has worked to identify gaps in youth mental health services; engage youth in program design; partner with local schools, public health services and other community organizations; adapt, translate, and produce resources; and offer activities and programs for young people to help fill some of the gaps. Through a community of practice and individualized support, CHSSN helped community organizations to build their knowledge, network with each other and problem solve on program implementation.

Learning Landscapes Journal : Education in a Pivotal Time : The Moment for Inspiration, Innovation, and Change - Leading English Education and Resource Network (LEARN) (2023)
Number of pages: 284

Mémoire : Consultation publique sur le plan d'action gouvernemental en matière de politque jeunesse au Québec - Provincial Employment Roundtable (PERT) (2023)

Charting the Course : 2022-2023 Year in Review - Youth for Youth Québec (Y4Y Québec) (2023)

Community Connections : Youth Perspectives on Mental Health - Youth for Youth Québec (Y4Y Québec) (2023)
Number of pages: 20

Community Connections : Youth Perspectives on Mental Health - Youth for Youth Québec (Y4Y Québec) (2022)
Number of pages: 17

Newsletter - Youth for Youth Québec (Y4Y Québec) (2022)
issued: November, 2022/December, 2022 Number of pages: 12

Newsletter - Youth for Youth Québec (Y4Y Québec) (2022)
Number of pages: 10

Latest Y4Y Quebec Research Outlines What Makes Quebec’s English-Speaking Youth (ESY) a Unique Set of Civic Actors: Quebec’s ESY Speak on the Driving Forces Behind their Civic Engagement. - Winrow, Adrienne (2022)

Learning Disabilities in Quebec : Potential Barriers in French Language Learning for English-Speaking Youth - Alder, Helen (Youth for Youth Québec (Y4Y Québec), 2022)

Newsletter - Youth for Youth Québec (Y4Y Québec) (2022)
Number of pages: 9

Civic Engagement Motivations and Barriers for English-Speaking Quebec Youth - Nykoluk, Brock (2022)
As such, to better understand Québec’s civic land- scape, civic engagement for ESQY ought to receive more scholarly attention. This report aims to help fill this gap by answering the following questions: How do ESQY characterize the motivations behind their civic engagement? How do ESQY characterize the barriers that hinder their civic engagement?

Newsletter - Youth for Youth Québec (Y4Y Québec) (2022)
Number of pages: 8

The Importance of School Support on the Mental Health of LGBTQIA2S+ Youth in Québec : Policy Brief - Piccolo, Lexie (Youth for Youth Québec (Y4Y Québec), 2022)
LGBTQIA2S+ youth face unique stressors. Québec isfairly inclusive as the province has prohibited discrimination of gender identity and sexual orientation in section 10 of the Québec Charter of Human Rights and Freedoms and urges for sexuality education to be a part of school curriculum. Although the province’s efforts have likely provided some relief to LGBTQIA2S+ Québec youth, reports of bullying and lack of support remain significant, especially in rural regions. Homophobic discrimination is directly and indirectly related to well-being as it can lead to feelings of isolation, which in turn leads to poorer mental health (Blais et al., 2014; Garcia et al., 2020). This is especially true for rural towns across Québec as the lack of queer representation prompts homophobic remarks and leads queer youth to feel alone (Dicaire, 2021). Given the amount of time youth spend in high-school, support within these facilities is essential. Research demonstrates that support systems for LGBTQIA2S+ youth, as well as education about this community within high-schools, may better the mental health of queer youth. In the absence of these tools, their mental health may languish.

Newsletter - Youth for Youth Québec (Y4Y Québec) (2022)
Number of pages: 8

Newsletter - Youth for Youth Québec (Y4Y Québec) (2022)
Number of pages: 7

Report on the Education and Vitality Forum : Overview - Macris, Antonia; QUESCREN (2022)

Sense of Belonging Among English-speaking Youth in Québec : Confronting Isolation Through Digital Community Building - Pettem, Alexandre (Youth for Youth Québec (Y4Y Québec), 2022)
Since the onset of Covid-19, community has come to inhabit a digital medium for many of Québec’s English-speaking youth. But what does this mean in concrete terms? How is this linguistic minority using social media, and in what manner are they experiencing this digital shift? Will they want to keep having online events going forward? Our paper observes the digital behavior of young (aged 16-30) English-speaking Québecers from March 2020 until the current moment in the pandemic’s development.

Newsletter - Youth for Youth Québec (Y4Y Québec) (2022)
Number of pages: 10

Déclaration sur le refus du gouvernement de la Coalition Avenir Québec de céder sur les dispositions concernant les étudiants des cégeps anglophones - Jennings, Marlene; Korakakis, Katherine; Lamoureux, Dan; Murphy, Rosemary (2022)

Statement on Coalition Avenir Québec Government’s Refusal to Budge on Provisions for English-speaking CEGEP Students - Jennings, Marlene; Korakakis, Katherine; Lamoureux, Dan; Murphy, Rosemary (2022)

Newsletter - Youth for Youth Québec (Y4Y Québec) (2022)
Number of pages: 8

A 5-Year Strategic Plan to Help Guarantee the Ongoing Vitality of Quebec’s English-speaking Youth : 2022-2027 - Youth for Youth Québec (Y4Y Québec) (2022)
The Plan is meant to articulate the needs, the issues, and the priorities of Québec’s English-speaking youth community (ages 16 – 30) It is a living document that will be reviewed and adapted over the 5-year span to reflect the changing needs within the community and the world.

Annex : A 5-Year Strategic Plan to Help Guarantee the Ongoing Vitality of Quebec’s English-speaking Youth : 2022-2027 - Youth for Youth Québec (Y4Y Québec) (2022)

Newsletter - Youth for Youth Québec (Y4Y Québec) (2022)
Number of pages: 9

Concert Series to Highlight Talents of Young Musicians Celebrating Local Heritage in the Sonorous Acoustics of St George Anglican Church - Centre for Access to Services in English (CASE) (2022)

Newsletter - Youth for Youth Québec (Y4Y Québec) (2022)
Number of pages: 10

Newsletter - Youth for Youth Québec (Y4Y Québec) (2022)
Number of pages: 9

Communauté du CHSSN NetLink - Community Health and Social Services Network (CHSSN) (2022)
Number of pages: 6

Community NetLink - Community Health and Social Services Network (CHSSN) (2022)
Number of pages: 6

Sondage Youth Pulse Check : Principales conclusions - Community Health and Social Services Network (CHSSN) (2022)

Youth Pulse Check Survey : Key Findings - Community Health and Social Services Network (CHSSN) (2022)

Booklet for Young Workers : Everything you Need to Know for your First Job - Montérégie West Community Network (MWCN); Educaloi (2022)

Initiative sur la jeunesse et la santé mentale : Rapport d’évaluation - Nigam, Sunita (Community Health and Social Services Network (CHSSN), 2022)

Sondage Youth Pulse Check : Rapport des résultats du sondage - Nigam, Sunita (Community Health and Social Services Network (CHSSN), 2022)
This document outlines the most important findings of the Youth Pulse Check, a mental health survey filled out by 456 English-speaking youth between the ages of 18-29 from 14 regions across the province of Quebec. Although 90% of respondents said they struggled at least somewhat often with their mental wellbeing and 81% of respondents, said that the COVID-19 pandemic has increased their struggles to feel well at a level 3 or more on a scale of 1 to 5, the survey revealed that many English-speaking youth feel there are significant gaps and barriers in accessing mental health services in their region. If many youth reported having sought out help in the past without success—meeting with barriers such as long wait lists, the prohibitive costs of mental health support, or the unavailability of services in English— other youth reported not having sought out help because of a lack of information about services to which they might turn.

Youth Mental Health Initiative : Evaluation Report - Nigam, Sunita (Community Health and Social Services Network (CHSSN), 2022)

Youth Pulse Check : Survey Results Report - Nigam, Sunita (Community Health and Social Services Network (CHSSN), 2022)
This document outlines the most important findings of the Youth Pulse Check, a mental health survey filled out by 456 English-speaking youth between the ages of 18-29 from 14 regions across the province of Quebec. Although 90% of respondents said they struggled at least somewhat often with their mental wellbeing and 81% of respondents, said that the COVID-19 pandemic has increased their struggles to feel well at a level 3 or more on a scale of 1 to 5, the survey revealed that many English-speaking youth feel there are significant gaps and barriers in accessing mental health services in their region. If many youth reported having sought out help in the past without success—meeting with barriers such as long wait lists, the prohibitive costs of mental health support, or the unavailability of services in English— other youth reported not having sought out help because of a lack of information about services to which they might turn.

Annual Report 2021-2022 - Youth for Youth Québec (Y4Y Québec) (2022)

Newsletter - Youth for Youth Québec (Y4Y Québec) (2021)
Number of pages: 12

Peer-reviewed by Fifth-graders : International Science Journal Brings Drummondville Students to the Frontier of Cutting Edge Discoveries - Centre for Access to Services in English (CASE) (2021)

Newsletter - Youth for Youth Québec (Y4Y Québec) (2021)
Number of pages: 10

Newsletter - Youth for Youth Québec (Y4Y Québec) (2021)
Number of pages: 11

Newsletter - Youth for Youth Québec (Y4Y Québec) (2021)
Number of pages: 13

Y4Y Québec Calls on the Legault Government to Consult with More Members of the English-speaking Community, and Youth in Particular, During Upcoming Bill 96 Hearings - Youth for Youth Québec (Y4Y Québec) (2021)

Protecting the Respiratory Health of Québec's Youth Population - Pattem, Alexandre (Youth for Youth Québec (Y4Y Québec), 2021)
Transportation traffic is one of the main sources of nitrogen dioxide (NO2), whether it emerges from trucks, buses, or car emissions (Government of Québec 2021). NO2 is formed from the “liberation of nitrogen contained in fuel and nitrogen contained in combustion air during combustion processes” (Government of Canada 2013). When released, NO2 has negative effects on human respiratory systems, especially those of teenagers and children (Wing, Sam E. et al 2018, 1-2). Growing evidence demonstrates that systems of asthma, for example, are likely to be aggravated or triggered in this youth segment of the population (Gillespie-Bennett, J. et al 2011, 303).

Newsletter - Youth for Youth Québec (Y4Y Québec) (2021)
Number of pages: 8

Newsletter - Youth for Youth Québec (Y4Y Québec) (2021)
Number of pages: 10

Le projet de loi 96 manque de perspective pour les jeunes et risque de créer de nouelles divisions entre les communautés linguistuques - Youth for Youth Québec (Y4Y Québec) (2021)

Newsletter - Youth for Youth Québec (Y4Y Québec) (2021)
Number of pages: 10

Did the Black Lives Matter Movement Help English-speaking Black Young Adults in Quebec Recover from the Damaging Psychological Effects of the COVID-19 Pandemic? - Koestner, Richard; Holding, Anne C. (Quebec English-speaking Communities Research Network (QUESCREN), 2021)
The historic events of the spring of 2020—the collision of the worst public health crisis in a century and the largest Black civil rights movement in half a century—offer a unique opportunity to examine how the frustrations and hopes of English-speaking Black young adults were affected. We sought to understand the potentially competing impacts that the public health and social justice crises have had on the young adults in their communities. Quebec has the second largest Black population in Canada (after Ontario), with 27% of Canada’s total Black population. Quebec’s Black population has doubled in size in the past 20 years, with 325,000 people currently living here. This population is predominantly French speaking (80%), and it is concentrated in the Montreal metropolitan area (over 90%). The Black population tends to be younger than the Canadian average, and its members are more likely to be first-generation Canadians.
Parallel title: QUESCREN Working Paper no.4

Youth Volunteer Retention in Québec - Lopes-Luchak, Milla (Youth for Youth Québec (Y4Y Québec), 2021)
Volunteers are major contributors to nonprofit organizations in Québec and across Canada. Despite their contributions, studies reveal that volunteer retention is an aspect that remains neglected (Merrilees, Miller & Yakimova, 2020). There are many reasons why people give their time and remain in the same nonprofit. Consequently, there is no individual factor that guarantees retention; it differs depending on age group, gender, socio-economic background, area of volunteerism, etc. Improving retention is in the best interest of nonprofits. Although youth are the age group that volunteer the most (according to Volunteers Canada), Québec is the province with the lowest rate (as stated by statcan) and has much to learn from the rest of the country.

Youth Entrepreneurship Guide - Fequet, Shelley; Fequet, Latesha; Roberts, Ashley (Coasters Association, 2021)
This guide is intended for young adults between the ages of 18-35. Its purpose is to help guide and support individuals through the process of creating their own business and to identify the resources needed to be successful. The development of this guide was supported by the members of the HOME Committee. Partners represented on the HOME Committee include; Community Economic Development and Employability Committee (CEDEC), Centre de services scolaire du Littoral. Centre lntegre de Sante et de Services Sociaux de la Cote-Nord (CISSS), Coasters Association and the MRC du Golfe-du-Saint-Laurent.

Newsletter - Youth for Youth Québec (Y4Y Québec) (2021)
Number of pages: 11

Newsletter - Youth for Youth Québec (Y4Y Québec) (2021)
Number of pages: 9

Supporting Youth Mental Health in and through the Arts : An Evidence Base and Guide for Teaching Artists - Kukkonen, Tiina (2021)

Newsletter - Youth for Youth Québec (Y4Y Québec) (2021)
Number of pages: 6

L'exode des jeunes anglophones du Québec - Ciamarra, Nadine; Lamarre, Patricia; Donovan, Patrick; O'Donnell, Lorraine (Quebec English-speaking Communities Research Network (QUESCREN), 2021)
Parallel title: Résumé de recherche en éducation no 7
Keywords: Official Language Minority Community (OLMC)

Outmigration of Quebec's English-speaking Youth - Ciamarra, Nadine; Lamarre, Patricia; Donovan, Patrick; O'Donnell, Lorraine (Quebec English-speaking Communities Research Network (QUESCREN), 2021)
Parallel title: Education Research Brief no. 7
Keywords: Official Language Minority Community (OLMC)

Annual Report 2021 - Committee for Anglophone Social Action (CASA) (2021)

Rapport Annuel 2021 - Committee for Anglophone Social Action (CASA) (2021)

Communauté du CHSSN NetLink - Community Health and Social Services Network (CHSSN) (2021)
Number of pages: 10

Community NetLink - Community Health and Social Services Network (CHSSN) (2021)
Number of pages: 6

Life without Compromise : Youth Forum 2021 - Kayla; Fequet, Latesha (2021)

Annual Report 2020-2021 - Youth Employment Services (YES) (2021)
As a not-for-profit organization, YES enriches the community by providing English-language support services to help Quebecers find employment and start and grow businesses. YES Employment + Entrepreneurship has been broadening access to opportunities for Quebec’s English-speaking community for over 25 years now. As we reflect on the organization’s 25th anniversary in the midst of the pandemic, we are reminded of the vital importance of our career and business support services.

Rapport annuel 2020-2021 - Youth Employment Services (YES) (2021)
En qualité d’organisme sans but lucratif, YES contribue à l’enrichissement de la communauté en offrant des services de soutien en anglais pour aider les québécois à trouver un emploi ou démarrer ou développer leurs entreprises. Depuis plus de 25 ans, YES Emploi + Entrepreneuriat facilite l’accès à différentes opportunités de croissance auprès de la communauté d’expression anglaise du Québec. Célébrer le 25e anniversaire de notre organisation en pleine pandémie nous rappelle à quel point nos services d’accompagnement à l’emploi et d’aide aux entreprises sont d’une importance vitale.

Toujours au rendez-vous : Rapport annuel 2021 - Youth Employment Services (YES) (2021)

Annual Report 2020-2021 - Youth for Youth Québec (Y4Y Québec) (2021)

Newsletter - Youth for Youth Québec (Y4Y Québec) (2020)
Number of pages: 8

Forum for Youth Insights : Career and Education Orientations for the Post-COVID-19 World - Cohen, Eric (Quebec English-speaking Communities Research Network (QUESCREN), 2020)
The kids are (mostly) alright! That message was made loud and clear during a fascinating discussion when a group of passionate thinkers, educators, students, and speakers got together virtually on October 25, 2020, for Concordia University’s Forum for Youth Insights. An initiative of the Quebec English-Speaking Communities Research Network through its Inter-Level Educational Table, in collaboration with Youth 4 Youth Québec and the Black Community Resource Centre, this year’s forum had a special theme : Career and Education Orientations for the Post-COVID-19 World. In a nutshell, it was an opportunity for students to understand the new realities of the post-COVID-19 experience and how to navigate the sometimes confusing road ahead. Spoiler alert : We’re gonna be alright (but we need to recalibrate slightly).
Parallel title: Report : Key Insights and Takeaways

Forum sur les perspectives jeunesse : orientations professionnelles et éducatives dans le monde post-COVID-19 - Cohen, Eric (Quebec English-speaking Communities Research Network (QUESCREN), 2020)
La jeunesse va (globalement) bien ! Ce message a été exprimé haut et fort lors d’une discussion captivante entre intellectuels, éducateurs, étudiants et conférenciers passionnés, qui s’est tenue virtuellement le 25 octobre 2020 dans le cadre du Forum sur les perspectives jeunesse de l’Université Concordia. L’événement a eu lieu à l’initiative du Réseau de recherche sur les communautés québécoises d’expression anglaise, par l’entremise de sa Table d’éducation interordres et en collaboration avec Youth 4 Youth Québec et le Centre de ressources de la communauté noire. Cette année, le forum avait un thème bien particulier : Orientations professionnelles et éducatives dans le monde post-COVID-19. En résumé, l’occasion a été donnée aux étudiants de saisir les nou- velles réalités de ce « monde d’après » afin qu’ils sachent comment s’engager sur la voie parfois déconcertante qui s’ouvre à eux. Alerte au divulgâcheur : tout va bien aller (mais il nous faudra procéder à quelques ajustements).
Parallel title: Rapport sue les idées et enseignements du forum

Forum for Youth Insights 2020 - Quebec English-speaking Communities Research Network (QUESCREN) (2020)

Newsletter - Youth for Youth Québec (Y4Y Québec) (2020)
Number of pages: 4

Newsletter - Coasters Association (2020)
Number of pages: 4

Newsletter - Youth for Youth Québec (Y4Y Québec) (2020)
Number of pages: 7

Newsletter - Youth for Youth Québec (Y4Y Québec) (2020)
Number of pages: 9 Issued: July, 2020/August, 2020

10 Innovative Projects to Assist Vulnerable English-speaking Youth and Seniors - Quebec Community Groups Network (QCGN) (2020)

Newsletter - Youth for Youth Québec (Y4Y Québec) (2020)
Number of pages: 6

Y4Y Quebec Calls for Support for English-speaking Youth as Quebec Plans to Reopen the Economy - Youth for Youth Québec (Y4Y Québec) (2020)

Profil de la jeunesse anglophone de la Gaspésie-Îles-de-la-Madeleine - Regional Individual Employment Services & Support (RIESS) (Committee for Anglophone Social Action (CASA), 2020)
Ce profil de la situation de la jeunesse anglophone de la Gaspésie et des Îles-de-la-Madeleine a été commandité par trois organisations communautaires : le Comité pour l’action sociale anglophone (CASA), le Conseil des Madelinot·e·s anglophones (CAMI) et Vision Gaspé-Percé Now. Des travaux de recherche-action fondés sur une approche participative et communautaire ont servi de base au développement de ce profil. Ce faisant, l’étude sur laquelle le présent document se fonde permet d’avoir un portrait des réalités propres à la jeunesse, développé par les jeunes elleux-mêmes; ceci permettra de travailler plus efficacement à la résolution des enjeux et des difficultés auxquels ils et elles font face dans les différentes communautés de la région. Une méthode d’approche mixte a ainsi été développée via la combinaison d’une enquête en ligne et de groupes de discussions sur des sujets liés à l’émigration, à l’éducation, à l’emploi, à la vie sociale, aux services, etc. Au total, 438 jeunes de 15 à 35 ans ont participé à l’enquête en ligne, et neuf groupes de discussion ont été instaurés sur un total de six communautés regroupant 82 jeunes.

Profile of English-speaking Youth : Gaspésie-Îles-de-la-Madeleine - Regional Individual Employment Services & Support (RIESS) (Committee for Anglophone Social Action (CASA), 2020)
Three community organizations commissioned this profile of the situation of young people in the Gaspésie-Îles-de-la-Madeleine region: the Committee for Anglophone Social Action (CASA), the Council for Anglophone Magdalen Islanders (CAMI) and Vision Gaspé-Percé Now. A study grounded in community-based participatory action research was developed, with the goal of hearing directly from young people about their realities in order to take action on issues affecting them in the region’s communities. A mixed methods approach combined an on-line survey with focus group discussions exploring questions related to out-migration, education, employment, social life, services and more. A total of 438 young people aged 15-35 filled out the survey and nine focus groups were held in a total of six communities with a total of 82 youth.

Profile of English-speaking Youth : Gaspésie-Îles-de-la-Madeleine - Richardson, Mary; Zettl, Mary; Harrison, Kim (Community Health and Social Services Network (CHSSN), 2020)
Three community organizations commissioned this profile of the situation of young people in the Gaspésie-Îles-de-la-Madeleine region: the Committee for Anglophone Social Action (CASA), the Council for Anglophone Magdalen Islanders (CAMI) and Vision Gaspé-Percé Now. A study grounded in community-based participatory action research was developed, with the goal of hearing directly from young people about their realities in order to take action on issues affecting them in the region’s communities. A mixed methods approach combined an on-line survey with focus group discussions exploring questions related to out-migration, education, employment, social life, services and more. A total of 438 young people filled out the survey and nine FGD were held in a total of six communities (with a total of 82 youth).

Newsletter - Youth for Youth Québec (Y4Y Québec) (2020)
Number of pages: 6

Redefining the Black Experience in Montreal: One Institution at a Time - The Project Woke Interns (Black Community Resource Centre (BCRC), 2020)
Project Woke interns identified and investigated three critical themes affecting the Black community in Montreal. An analysis of societal issues and Canada’s Anti-Racism Strategy Project revealed harmful anti-human rights gaps affecting the Black Community. The findings from several consultations further validated these gaps. A comprehensive list of recommendations is included along with next steps as a continuation to advance Black human rights in Montreal, and elsewhere, along with the support of government and non-government actors.

Newsletter - Youth for Youth Québec (Y4Y Québec) (2020)
Number of pages: 6

Evaluation Report - Holley, Paul (Youth for Youth Québec (Y4Y Québec), 2020)
The following evaluation report fulfills a key deliverable of a broader project funded by Canadian Heritage and titled Best Practices in Community Engagement for the English Speaking Youth Population in Quebec, which was implemented by Youth 4 Youth (Y4Y) Quebec from April 1, 2019 to March 31, 2020. The key objective of this project was to boost youth engagement and participation in political and community life in Quebec. Y4Y successfully accomplished this objective by engaging over 1,000 youth through a series of 30 community consultations, 12 focus groups, and a youth survey delivered on-line and in-person with 520 respondents. The focus of this report is on the key findings from the survey, which targeted Englishspeaking youth ages 16 to 30 from across the province and collected quantitative and qualitative information on youth media consumption and community engagement activities. A gender-based analysis of key survey findings was also conducted and is presented in this report along with a set of recommendations for community organizations serving Quebec’s English-speaking youth population.

Newsletter - Youth for Youth Québec (Y4Y Québec) (2020)
Number of pages: 13

Newsletter - Coasters Association (2020)
Number of pages: 4

Newsletter - Youth for Youth Québec (Y4Y Québec) (2020)
Number of pages: 13

Newsletter - Youth for Youth Québec (Y4Y Québec) (2020)
Number of pages: 8 Issued: December, 2020/January, 2021

Profil des jeunes anglophones des Laurentides 15 à 29 ans - 4Korners (2020)
Selon les données publiées par l’Institut de la statistique du Québec en 2020, la population vivant dans les régions administratives de la province a considérablement changé de 2019 à 2021 en raison des répercussions sociales directes de la pandémie de COVID-19 et de ses conséquences sur la migration, la mobilité, l’attractivité de la main-d’oeuvre, la conciliation travail-famille, les habitudes de vie et les loisirs. Ainsi, on estime que 632 000 habitants vivaient dans la région des Laurentides au 1er juillet 2020, marquant une augmentation de 17,7 % pour l’année 2019-2020; ce pourcentage est plus élevé que le taux moyen de l’ensemble de la province (8,5 %) pour cette année. De fait, il est important de souligner que cette région présente la plus forte augmentation depuis le début de la pandémie en mars 2020.

Profile of Laurentian English-speaking Youth 15-29 - 4Korners (2020)
According to data published by the Institut de la statistique du Québec in 2020, the population living in the administrative regions of the province has significantly changed between 2019 and 2021, being directly affected by the social impacts caused by the COVID-19 pandemic and its implications for out-migration, mobility, workforce attractivity, work/life balance, lifestyle habits and leisure activities. As a result, it is estimated that 632,000 inhabitants were living in the Laurentian region as of July 1, 2020. This represents an increase of 17.7% for the year 2019-2020, which is higher than the average rate across the province (8.5%) for that year. In fact, it is important to highlight that this region presents the largest increase since the outbreak of the pandemic in March 2020.

An Uncertain Future for the Future of Québec : Policy Brief on the Under Employment of English-speaking Youth in the Quebec Civil Service - Lawler, Madeleine (Youth for Youth Québec (Y4Y Québec), 2020)
Since the start of the COVID-19 global pandemic, post-secondary students have been amongst the hardest hit economically. In the span of two months, the unemployment rate amongst Canadian post-secondary students almost doubled, and less than a quarter of previously employed students continued working their regular hours. The global pandemic further exacerbated pre-existing issues of economic vulnerability and underemployment amongst English-speaking youth in Quebec. According to a 2018 CHSSN report, the unemployment rate amongst English-speaking youth was 13.3%, whereas that of their Frenchspeaking counterparts was 9.8%.2 Across different industries, the under-employment of Englishspeaking youth is perhaps the most pitiful within the Quebec civil service. In general, anglophones have represented between 0.7% and 1% of the provincial civil service for nearly half a century, despite representing 7.4% of the population in 2016

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2020)
Number of pages: 28

Report on Youth Employability in the Greater Quebec City Region - Voice of English-speaking Quebec (VEQ) (2020)
In the winter of 2019-2020, we conducted a survey of English-speaking youth aged 15 to 29 as well as six focus groups at the English high schools in the region to support two projects related to youth employability. Through our needs analysis, we sought to evaluate youth knowledge and/or use of the services offered by the Carrefour jeunesse-emploi centres as well as to gain some insights into the postsecondary education and career plans of the students at the local English high schools. These results are meant to provide a snapshot of the perspectives of Englishspeaking youth on employment in the Greater Quebec City region at this time. Though small in scope and sample size (53 survey participants, 32 focus group participants), this study captures the very real hopes and frustrations of our minority population. At the same time, it also proposes some very concrete and achievable outcomes. We hope that this document can serve as a springboard for employers and service providers to work with us, and members of our community, to increase the employability of English-speaking youth in the Greater Quebec City region. Let’s build a better future for all Québécois.

Who We Are - Youth Employment Services (YES) (2020)

Annual Report 2020 - Youth for Youth Québec (Y4Y Québec) (2020)